Strategies for Improving Teacher Performance: A PRISMA-Based Systematic Literature Review on Transformational Leadership, Professional Competence, and Self-Efficacy - Wati, Rosna; Hardienata, Soewarto; Lathifah, Zahra Khusnul (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2026)
Teacher performance is a key determinant of educational quality and learning effectiveness across various global educational contexts. Although numerous studies have examined the factors influencing teacher performance, empirical synthesis focused on the integration of transformational leadership, professional competence, and self-efficacy in recent years remains limited. This study aims to synthesize and analyze the latest empirical findings on strategies for improving teacher performance through these three variables. This study employed the Systematic Literature Review (SLR) method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Articles were obtained from Scopus, Web of Science, and ERIC databases, published between 2020 and 2025. Based on the identification, screening, and eligibility evaluation processes according to inclusion and exclusion criteria, 30 empirical articles were selected and analyzed in depth. The synthesis results indicate that transformational leadership consistently has a positive effect on teacher performance, both directly and through increased motivation and professional commitment. Professional competence has been shown to be a significant predictor of learning quality, instructional effectiveness, and student learning outcomes. Meanwhile, self-efficacy emerged as a key psychological factor that strengthens teachers' resilience, pedagogical innovation, and adaptability to changes in the educational environment. The integration of findings yielded a multidimensional conceptual model that positions transformational leadership as a structural factor, professional competence as a capability factor, and self-efficacy as a psychological factor that interact to improve teacher performance. This study provides theoretical contributions through the consolidation of current empirical evidence and practical implications for the development of evidence-based school leadership policies and teacher capacity-building programs.